Quantitative Scanning Transmission Electron Microscopy of Electronic and Nanostructured Materials - Yankovich, Andrew (My University, 2015)
This thesis reports studies of electronic and nanostructured materials by advanced electron microscopy (EM) techniques, including scanning transmission electron microscopy (STEM), position averaged convergent beam electron diffraction (PACBED), X-ray energy dispersive spectroscopy (EDS), and electron energy loss spectroscopy (EELS). This work enhanced the understanding of the microstructure, defects, and composition of Ga-doped ZnO thin films, Sb-doped ZnO nanowires, and InGaN quantum well (QW) based light emitting diode (LED) structures, and helped develop structure ? property relationships for these materials. A new technique, non-rigid registration of STEM images, was developed and applied to make high-precision measurements of the atomic structure of Pt nanocatalysts and Au nanoparticles, and to improve the quality of STEM EDS spectrum images. ZnO is the first major topic. Ga-doped ZnO is a candidate transparent conducting oxide material. The microstructure of GZO thin films grown by molecular beam epitaxy under metal-rich conditions on sapphire, O-rich conditions on sapphire, and metal-rich conditions on GaN were examined using various EM techniques. The microstructure, prevalent defects, and polarity in these films strongly depend on the growth conditions and substrate. In ZnO nanowires, collaborators have demonstrated the first stable p-type ZnO using Sb doping. Using Z-contrast STEM, we showed that an unusual microstructure of Sb-decorated head-to-head inversion domain boundaries and internal voids contain all the Sb in the nanowires and cause the p-type conduction. InGaN thin films and InGaN / GaN quantum wells (QW) for light emitting diodes are the second major topic. Low-dose Z-contrast STEM, PACBED, and EDS on InGaN QW LED structures grown by metal organic chemical vapor phase deposition show no evidence for nanoscale composition variations, contradicting previous reports. However, a new extended defect in GaN and InGaN was discovered. The defect consists of a faceted pyramid-shaped void that produces a threading dislocation along the [0001] growth direction, and is likely caused by carbon contamination during growth. Non-rigid registration and high-precision STEM of nanoparticles is the final topic. Non-rigid registration (NRR) is a new image processing technique that corrects distortions arising from the serial nature of STEM acquisition that previously limited the precision of locating atomic columns and counting the number of atoms in each column in STEM images. NRR was used to demonstrate sub-picometer precision in STEM images of single crystal Si and GaN, the best reported in EM. NRR was then used to measure the atomic surface structure of Pt nanoacatalysts and Au nanoparticles which revealed new bond length variation phenomenon of surface atoms. In addition, NRR allowed for measuring the 3D atomic structure of the nanoparticles with less than 1 atom uncertainty, a long standing problem in electron microscopy. Finally, NRR was adapted to EDS spectrum images, significantly enhancing the signal to noise ratio and resolution of an EDS spectrum image of Ca-doped NdTiO3 compared to conventional methods.
Keywords: electron microscopy, microstructure, materials science